Properties of certain semigroups and their potential as platforms for cryptosystems - Kropholler, P.H.; Pride, S.J.; Othman, W.A.M.; Wong, K.B.; Wong, P.C. (Springer Verlag (Germany), 2010)
In this paper, we study some properties of semigroups with presentation aOE (c) a,b ; a (p) =b (r) ,a (q) =b (s) >. We will also study their potential as platforms for the Diffie-Hellman key exchange protocol.